2013
DOI: 10.2478/v10114-011-0026-7
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary results of soil respiration in beech, spruce and grassy stands

Abstract: Soil respiration constitutes the second largest flux of carbon between terrestrial ecosystems and the atmosphere. This study provides the preliminary results of soil respiration (Rs) observations in three different stands, including two types of young forest stands (beech and spruce) and grassy clearings. The average values of Rs ranged from 0.92 to 15.20 µmol CO 2 m -2 s -1 in the beech stand, from 1.14 to 11.26 µmol CO 2 m -2 s -1 in the spruce stand and from 0.96 to 12.92 µmol CO 2 m -2 s -1 in the grassy s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
0
2
0
1
Order By: Relevance
“…However, while the soil variables measured here could potentially be used as indicators of woodland ecosystem condition, further research is required to verify the extent to which they are generally applicable. Previous research has demonstrated that soil respiration in temperate forest stands can be very variable (Priwitzer et al, 2013) and rates are influenced by a wide range of factors including soil moisture and temperature, as well as the species present (Smith and Johnson, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…However, while the soil variables measured here could potentially be used as indicators of woodland ecosystem condition, further research is required to verify the extent to which they are generally applicable. Previous research has demonstrated that soil respiration in temperate forest stands can be very variable (Priwitzer et al, 2013) and rates are influenced by a wide range of factors including soil moisture and temperature, as well as the species present (Smith and Johnson, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Emissões em clima temperado são maiores no verão do que no inverno, independentemente do tipo de cobertura vegetal. [15][16][17] A quantificação das emissões de CO 2 também é tema relevante, e a busca por equipamentos de baixo custo e de fácil manuseio em campo tem sido constante. Dentre os métodos empregados, o da câ-mara dinâmica determina o fluxo de CO 2 emitido baseado na variação de concentração dos gases emitidos pelo solo no interior da câmara, 18 com determinação direta das concentrações por analisadores de gás infravermelho, também conhecido como IRGAS, do inglês, Infra Red Gas Analiser.…”
Section: Introductionunclassified
“…Dry periods (low soil moisture) may occur in this altitude, usually after the 220 th day, i.e. after the period of terminal growth (see also Priwitzer et al 2013). However, a certain influence of height growth rate by precipitation could be assumed due to the coincidence of peaks in both characteristics in spruce stands during 2009 (on the ca.…”
Section: Seasonal Dynamics Of Height Incrementmentioning
confidence: 99%